2002
DOI: 10.1021/ie020304p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Radiation on the Acetate-Catalyzed Hydrolysis of Phenyl Acetate at 25 °C

Abstract: In this paper we present the experimental results obtained from phenyl acetate hydrolysis in a microwave-irradiated environment and in water solutions containing catalytic acetate ions. The kinetics of the reaction were studied in an irradiated environment where radiation, at a frequency of 2.45 GHz, was given to the reacting system at a power of 0.500 ± 0.025 W. The energy absorbed by the reacting system was measured using a directional coupler, which can separate the radiation directed to the reactor from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…It was found that at 25 C, a substantial increase in reaction rate was observed in the microwave environment than in nonradiated environment. 261 But at 35 C, the kinetic constant was found to increase 16 fold from a nonradiated environment to an environment radiated with a microwave of 50 mW. As a result, the activation energy was reduced, illustrating the athermal effect of microwave.…”
Section: Athermal Applications Of Microwavesmentioning
confidence: 94%
“…It was found that at 25 C, a substantial increase in reaction rate was observed in the microwave environment than in nonradiated environment. 261 But at 35 C, the kinetic constant was found to increase 16 fold from a nonradiated environment to an environment radiated with a microwave of 50 mW. As a result, the activation energy was reduced, illustrating the athermal effect of microwave.…”
Section: Athermal Applications Of Microwavesmentioning
confidence: 94%
“…We have already presented a study to the scientific world in which we demonstrated at a constant temperature of 25°C, a modest increase in the reaction rate of phenyl acetate hydrolysis running in a radiated environment with respect to that running in a nonradiated environment (Carta, 2002). In the same work, we suggested the possibility that the increase could be attributed to a sort of catalytic effect of the microwave radiation.…”
Section: Introductionmentioning
confidence: 80%
“…The radiating apparatus was presented in a previous work by the same authors (Carta, 2002). Particular attention was paid to the design of the reactor.…”
Section: Experimental Procedures and Elaboration Of Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations